Ecological impacts of Assuit fertiliser factory in Upper Egypt: environmental implications and spatial distribution of natural radionuclides. Issue 5 (9th April 2023) - Massoud, Eheb; El-Taher, Atef; Najam, Laith Ahmed; Elsaman, Reda
ABSTRACT: In the present work, radioactivity level in 15 collected soil samples from the area around fertiliser factory in Upper Egypt has been measured using gamma ray Spectrometry due to radionuclides occurred naturally namely 226 Ra, 232 Th and 40 K to study the concentrations of these nuclides in this soil and determine the effect of Assuit fertiliser factory exhaust on radiological contents of surrounding Soil Samples in Assuit Province, Egypt. Activity concentrations of 226 Ra, 232 Th and 40 K for soil samples were measured by scintillation detector NaI (Tl), has recorded average values 49.45 ± 5.04, 59.113 ± 2.96 and 137.85 ± 6.89 Bq/kg, respectively. On the other hand the average value of radiological hazards affected on farmers and populations were 150.32 Bq/kg, 64.3 nG/h, 0.257, 0.544, 1.006, 0.246, 0.315 and 0.0788 mSv/y for radium equivalent activity, absorbed gamma dose, external and internal hazard indices, gamma index, indoor and outdoor effective dose, respectively. The absorbed dose, gamma index and the annual gonadal dose equivalent the radiological hazards were found higher than permissible level.